Rocky Horror : a behind-the-scenes look at the cult classic - Rock, Mick; Mohr, Tim (Harper Pop, 2025)
"Step behind the curtain of The Rocky Horror Picture Show with photographer Mick Rock in this one-of-a-kind slipcased collection of rarely seen photographs and behind-the-scenes anecdotes. Known as "the man who shot the seventies," Mick Rock had exclusive access to the set during the original filming of the now-iconic 1975 movie--and now, in honor of its 50th anniversary, his personal archive is wide open. This stunning volume captures the raw, behind-the-scenes magic of a film that would go on to become a cultural phenomenon. From candid moments with Tim Curry, Susan Sarandon, and Richard O'Brien to intimate shots of the cast between takes, every page offers a glimpse into the bold, bizarre, and beautiful world of Rocky Horror as it was being brought to life. Featuring a foreword by creator Richard O'Brien and hundreds of rare photographs, this stunning gift book is a visual love letter to the wild energy, fearless creativity, and sheer chaos that turned a low-budget musical into a beloved masterpiece. Alongside these vivid behind-the-scenes snapshots and anecdotes, readers also gain VIP access to interviews with members of the original cast and crew, as well as famous performers and creatives who are among the film's most fervent fans, including Joan Jett, Billy Corgan, Courtney Love, Juliette Lewis, Jinkx Monsoon, Duff McKagan, Anna Sui, Karen O, Trixie Mattel, Peaches, Norman Reedus, Cassandra Peterson (aka Elvira, Mistress of the Dark), and many, many more. Whether you're a devoted fan or just discovering the Time Warp, Mick Rock's Rocky Horror is dripping with the glam, grit, and rebellious spirit that made the movie a revolution in platform heels. Don't just shiver with antici--pation; dive into this timeless tribute and celebrate the global phenomenon that continues to resonate with audiences, generation after generation."--Publisher.